2-Deoxystreptamine Conjugates by Truncation-Derivatization of Neomycin - Floris L. van Delft; Floris P.J.T. Rutjes; Gerard W. Canters; Alessio Andreoni; Leandro C. Tabares; M. Waqar Aslam (MDPI AG, 2010)
A small library of truncated neomycin-conjugates is prepared by consecutive removal of 2,6-diaminoglucose rings, oxidation-reductive amination of ribose, oxidation-conjugation of aminopyridine/aminoquinoline and finally dimerization. The dimeric conjugates were evaluated for antibacterial activity with a unique hemocyanin-based biosensor. Based on the outcome of these results, a second-generation set of monomeric conjugates was prepared and found to display significant antibacterial activity, in particular with respect to kanamycin-resistant E. coli.